Model Kausalitas Intention to Continue Using E-Wallet Dana: Perceived Ease of Use, Perceived Security, dan User Satisfaction - Argy Wahyu Prabowo; Umi Widyastuti; Diena Noviarini (Teewan Journal Solutions, 2026)
This study aims to analyze the influence of perceived ease of use, Perceived Security, and User Satisfaction on the Intention to Continue Using the DANA e-wallet. The research is motivated by the growing use of e-wallets in Indonesia, particularly DANA, which calls for a deeper understanding of the factors influencing user loyalty and continued usage. This study employs a quantitative approach using a survey method and an instrument in the form of a questionnaire distributed online to active DANA users in the DKI Jakarta area. The data were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results show that Perceived Ease of Use and Perceived Security have a positive and significant effect on user satisfaction. Furthermore, User Satisfaction is proven to have a positive and significant effect on the Intention to Continue Using the DANA e-wallet. These findings highlight the importance of ease of use and a sense of security in enhancing User Satisfaction and encouraging continued use of e-wallet services.